Effect of Matrine on growth performance, gut health, and gut microbiota in chickens infected with avian pathogenic Escherichia coli - Ningning Mao; Yaming Yu; Jiqin Cui; Jin He; Yang Yang; Deyun Wang (Poultry Science)
Avian pathogenic Escherichia coli (APEC) is a major cause of avian colibacillosis. Matrine, a natural component derived from Sophora flavescens, exhibits various pharmacological effects, including anti-inflammatory and antioxidant activities. However, its role in mitigating APEC-induced intestinal damage in chickens remains insufficiently understood. This study aimed to explore the protective effects and potential mechanisms of matrine against APEC-induced intestinal damage. Chickens were administered matrine (10 or 20 mg/kg) from 6 days old for 5 days, followed by an APEC intraperitoneal injection on day 10. After 72 h of APEC infection, tissues were collected for analysis. Results indicated that pretreatment with matrine alleviated the symptoms of APEC infection in chickens, improving survival rates and promoting weight gain. Additionally, pretreatment with matrine reduced the secretion and gene expression of IL-1β, IL-6, and TNF-α in intestinal tissues, while enhancing serum SOD, GSH, and CAT activity, as well as gene expression levels in the intestine. Pretreatment with matrine reduced the levels of TLR4, MyD88, and NF-κB in intestinal tissues. Moreover, pretreatment with matrine ameliorated intestinal inflammation and pathological damage, restoring the expression of ZO-1, Occludin, and MUC2 in the intestine during APEC infection. Furthermore, pretreatment with matrine alleviated gut microbiota dysbiosis by lowering the abundance of harmful bacteria. In summary, matrine alleviated APEC-induced intestinal inflammation and damage, potentially by inhibiting NF-κB signaling pathway and reshaping the gut microbiota. These findings provide promising insights into the prevention and treatment of avian colibacillosis.